Post-Awareness Marketing: Rethinking Brand Communication in a Fragmented Market - Agus Sunaryo; Anna Krisdaningsih; Sugeng Eko Yuli Waluyo; Adil Abdillah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This research examines the transition from brand awareness to brand meaning within saturated digital ecosystems, specifically focusing on how global brands like Pepsi and Apple navigate the